2007
DOI: 10.3892/ijmm.20.4.451
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human rheumatoid arthritis synovial cell survival by hecogenin and tigogenin is associated with increased apoptosis, p38 mitogen-activated protein kinase activity and upregulation of cyclooxygenase-2

Abstract: Abstract. We conducted our study to assess the antiproliferative and proapoptotic potential of hecogenin and tigogenin, two saponins which are structurally similar to diosgenin. We particularly focused our attention on mitogenactivated protein kinase (MAPK) activation in relation to apoptosis but also with the COX-2 expression and activity. Rheumatoid arthritis (RA) synoviocytes were isolated from fresh synovial biopsies obtained from five RA patients undergoing hip arthroplasty. Measurement of cell proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
(50 reference statements)
2
13
0
1
Order By: Relevance
“…On the other hand, there are very few studies showing the anti-inflammatory activity of hecogenin (Peana et al, 1997) and none on its gastroprotection. Most of the literature data focus on diosgenin, also a steroidal sapogenin as hecogenin (Liagre et al, 2005(Liagre et al, , 2007a(Liagre et al, , 2007bMoalic et al, 2001;Shishodia and Aggarwal, 2006). Thus, the present study demonstrates, for the first time, the antiulcer property of hecogenin from A. sisalana, on experimental models of gastric ulceration in mice.…”
Section: Discussionsupporting
confidence: 61%
“…On the other hand, there are very few studies showing the anti-inflammatory activity of hecogenin (Peana et al, 1997) and none on its gastroprotection. Most of the literature data focus on diosgenin, also a steroidal sapogenin as hecogenin (Liagre et al, 2005(Liagre et al, , 2007a(Liagre et al, , 2007bMoalic et al, 2001;Shishodia and Aggarwal, 2006). Thus, the present study demonstrates, for the first time, the antiulcer property of hecogenin from A. sisalana, on experimental models of gastric ulceration in mice.…”
Section: Discussionsupporting
confidence: 61%
“…These results strongly suggest that MAPK pathways are closely involved in flavonol-rich RVHxR induced antiangiogenic process and likely upstream of VEGF expression. Considering that p38 MAPK is generally activated by genotoxic agents or apoptosis [36][37][38], activation of p38 MAPK by flavonolrich RVHxR may be associated with the apoptosis of RA FLS during antiangiogenic process.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by the research 260 group showed that hecogenin-and tigogenin-induced apoptosis of 261 RA-FLS is mediated through activation of p38 without affecting the 262 JNK and ERK pathways [26]. Activation of the p38 MAPK pathway 263 has been found to stimulate the expression of Cyr61, which 264 protects RA-FLS from apoptosis [27].…”
mentioning
confidence: 99%